LINGUOCULTURAL FEATURES OF PHRASEOLOGY IN UZBEK AND GERMAN LANGUAGES - Muminova Oftobkhon Karimovna (Journals Park Publishing, 2022)
This article briefly discusses phraseology in Uzbek and German. The views of the German linguist II Chernishyova on phraseology are theoretically illuminated.
Keywords: lingvoculturology; phraseology; paremia